Metacognition of Visual Short-Term Memory: Dissociation between Objective and Subjective Components of VSTM - Bona, Silvia; Cattaneo, Zaira; Vecchi, Tomaso; Soto, David; Silvanto, Juha (Frontiers in Psychology, 2013)
The relationship between the objective accuracy of visual-short term memory (VSTM) representations and their subjective conscious experience is unknown. We investigated this issue by assessing how the objective and subjective components of VSTM in a delayed cue-target orientation discrimination task are affected by intervening distracters. On each trial, participants were shown a memory cue (a grating), the orientation of which they were asked to hold in memory. On approximately half of the trials, a distractor grating appeared during the maintenance interval; its orientation was either identical to that of the memory cue, or it differed by 10 or 40 degrees. The distractors were masked and presented briefly, so they were only consciously perceived on a subset of trials. At the end of the delay period, a memory test probe was presented, and participants were asked to indicate whether it was tilted to the left or right relative to the memory cue (VSTM accuracy; objective performance). In order to assess subjective metacognition, participants were asked indicate the vividness of their memory for the original memory cue. Finally, participants were asked rate their awareness of the distracter. Results showed that objective VSTM performance was impaired by distractors only when the distractors were very different from the cue, and that this occurred with both subjectively visible and invisible distractors. Subjective metacognition, however, was impaired by distractors of all orientations, but only when these distractors were subjectively invisible. Our results thus indicate that the objective and subjective components of VSTM are to some extent dissociable.